2019
DOI: 10.1111/jrh.12368
|View full text |Cite
|
Sign up to set email alerts
|

Rural‐Urban Trends in Opioid Overdose Discharges in Missouri Emergency Departments, 2012‐2016

Abstract: Purpose Opioid overdose death rates rose 36% from 2015 to 2016 in Missouri, indicating a worsening of the opioid overdose epidemic. To better understand urban and rural differences in nonfatal opioid overdoses treated in Missouri emergency departments, this paper analyzed hospital billing data from emergency departments due to opioid overdose from 2012 to 2016. Methods Emergency department records meeting the opioid overdose case definition were aggregated into 6 progressively rural groups using the National C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…On the other hand, use of coal as a source of heating is more common in rural regions. These correlations are in line with existing research that has suggested that in recent years opioid epidemic has been expanding from rural regions to urban regions [23], [33]. Higher levels of education have been associated with healthier populations [34].…”
Section: Resultssupporting
confidence: 89%
“…On the other hand, use of coal as a source of heating is more common in rural regions. These correlations are in line with existing research that has suggested that in recent years opioid epidemic has been expanding from rural regions to urban regions [23], [33]. Higher levels of education have been associated with healthier populations [34].…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, 1 in 10 reported a rural residence. Rural and micropolitan counties have fewer resources such as infectious diseases and/or addiction providers and rehabilitation facilities, which necessitates a long commute to more urban medical centers [ 32 ]. These counties often lack robust emergency medical services to distribute life-saving interventions, such as naloxone [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rural and micropolitan counties have fewer resources such as infectious diseases and/or addiction providers and rehabilitation facilities, which necessitates a long commute to more urban medical centers [ 32 ]. These counties often lack robust emergency medical services to distribute life-saving interventions, such as naloxone [ 32 ]. Due to a lack of Medicaid expansion in Alabama, hospitals face financial hurdles when trying to care for their inpatients and safely transition them to outpatient settings [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%